2014
DOI: 10.1002/jaba.181
|View full text |Cite
|
Sign up to set email alerts
|

Training pouched rats to find people

Abstract: Giant African pouched rats equipped with video cameras may be a tenable option for locating living humans trapped under debris from collapsed structures. In the present study, 5 pouched rats were trained to contact human targets in a simulated collapsed building and to return to the release point after hearing a signal to do so. During test sessions, each rat located human targets more often than it located similar-sized inanimate targets on which it had not previously been trained and spent more time within 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Using the criteria described by Cox and Virues-Ortega (2015), we categorized participant FA outcomes after each medication change along two dimensions: changes in overall rate of behavior or addition or subtraction of an identified function. For one participant’s behavior (i.e., Ron’s SIB), medication had a suppressing or reducing effect as the rate of Ron’s SIB seemingly decreased across medication phases.…”
Section: Discussionmentioning
confidence: 99%
“…Using the criteria described by Cox and Virues-Ortega (2015), we categorized participant FA outcomes after each medication change along two dimensions: changes in overall rate of behavior or addition or subtraction of an identified function. For one participant’s behavior (i.e., Ron’s SIB), medication had a suppressing or reducing effect as the rate of Ron’s SIB seemingly decreased across medication phases.…”
Section: Discussionmentioning
confidence: 99%
“…They have helped identify many false‐negative samples over the past few years, and a recent study revealed a 44% increase in detections when using the giant pouched rats as a second line following light microscopy evaluation . More recent studies utilizing the extraordinary olfactory ability of giant pouched rats are focused on urban search‐and‐rescue training such as with collapsed buildings …”
Section: Introductionmentioning
confidence: 99%
“…8,10,11 More recent studies utilizing the extraordinary olfactory ability of giant pouched rats are focused on urban search-and-rescue training such as with collapsed buildings. 8,12,13 The purpose of this study was to describe ophthalmic examination findings and intraocular pressures (IOPs) in wild-caught African giant pouched rats (Cricetomys ansorgei and gambianus) from Tanzania and Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…A second critical expansion of our conceptualization of repetitive behavior comes from the recognition that discrete repetitive behaviors are exemplars of what appears to be a larger, generalized pattern of rigid, inflexible behavior or lack of response variability across multiple behavioral classes (Rodriguez and Thompson 2015). A striking example of this comes from eye-tracking studies that show a restricted and repetitive pattern of visual attention to a pictorial array of nonsocial items in children with ASD compared to typically developing children (Sasson et al 2008).…”
mentioning
confidence: 99%